Emerging Legal Response to Gender-Based Domestic Violence in Bangladesh: Analyzing the Scope and Limitations of Indigenous Legal Regime in light of International Treaties - Suvra, Anika Nower (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Gender-based domestic violence is a concerning global issue, causing significant physical and psychological harm to individuals. Family violence is increasingly recognized not only as a human rights concern but also as a matter of public welfare. Unfortunately, Bangladesh, being one of the world's poorest countries, experiences a high prevalence of domestic violence cases. While Bangladesh has been acknowledged by international frameworks like the UDHR, ICCPR, ICESCR, CEDAW, and DEVAW for protecting individuals, particularly women, from gender-based domestic violence, the implementation of these protections remains questionable. Although Bangladesh has enacted specific legislation to address domestic violence, there is a need to assess its effectiveness in safeguarding the rights of all victims, regardless of gender. This article aims to analyze the scope and limitations of the law in protecting individuals from domestic violence and ensuring their rights. Bangladesh faces challenges in ensuring gender-based rights, as domestic violence incidents involving men, children, and transgender individuals often go unreported. Through this research paper, the author focuses on the objectives of regulations, the enforcement of legal requirements, and the existing limitations within the law to prevent domestic violence and ensure justice for all affected individuals.